1998
DOI: 10.1021/bi980871+
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to Substrate Specificity and Transport of Nonconserved Residues in Transmembrane Domain 12 of Human P-Glycoprotein

Abstract: P-glycoprotein (Pgp), the product of the MDR1 gene, confers multidrug resistance on cancer cells by ATP-dependent extrusion of anticancer drugs. Biochemical and genetic studies with Pgp have identified the putative transmembrane (TM) region 12 (residues 974-994) as a major region involved in drug interactions with amino acid residues conserved among Pgp family members shown to be essential for transport. To determine whether nonconserved residues might be involved in substrate specificity, seven amino acid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 18 publications
4
52
0
Order By: Relevance
“…The topologically comparable transmembrane helix in P-gp, due to the five additional NH 2 -proximal TMs in MRP1/mrp1, is TM12, which has been demonstrated to play an important role in substrate specificity and drug binding. (35). Use of the thiol-reactive substrate, dibromobimane, together with cysteine-scanning mutagenesis has confirmed that hydrophobic residues Leu 975 , Val 982 , and Ala 985 in TM12 are important for the interaction of substrates with P-gp (36,37).…”
Section: Discussionmentioning
confidence: 96%
“…The topologically comparable transmembrane helix in P-gp, due to the five additional NH 2 -proximal TMs in MRP1/mrp1, is TM12, which has been demonstrated to play an important role in substrate specificity and drug binding. (35). Use of the thiol-reactive substrate, dibromobimane, together with cysteine-scanning mutagenesis has confirmed that hydrophobic residues Leu 975 , Val 982 , and Ala 985 in TM12 are important for the interaction of substrates with P-gp (36,37).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the characterization of novel MDR-1 variants may be useful for the development of novel inhibitors that specifically modulate the activity of the individual types of MDR-1. The feasibility of using inhibitors of individual (artificially created) MDR-1 variants and their potential therapeutic application has recently been demonstrated in a model system (30,31). Mickley et al have recently described two genetic polymorphisms in MDR-1 at positions 2677 and 2995 in exons 21 and 24 (22).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, experiments with artificially introduced MDR-1 mutations show clearly that PGP reacts quite sensitively to amino acid alterations. Mutations that change amino acids can alter the substrate spectrum of PGP, the effectiveness of transport, and also the sensitivity of PGP toward inhibition with specific inhibitory substances (2,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). It is clear that some naturally occurring mutations and alleles-if they exist, and if we can discover themmay show similar effects.…”
mentioning
confidence: 99%
“…Considerable effort has been invested in characterizing drug resistance changes caused by Pglycoprotein mutations [52,53,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. P-glycoprotein mutations that have appeared in cultured cells selected for resistance to particular drugs [130][131][132], and mutations incorporated by site-directed mutagenesis have been evaluated [52,53,127,129,[134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: B Analysis Of Mutations Affecting the Drug Binding Sites Ofmentioning
confidence: 99%